Perfil hormonal anual de machos e fêmeas adultos de saguis (callithrix jacchus) - Rego, Márcio Vinícius (2008)
Many behavioral and biological variables of animals are expressed in the form of biological rhytms, down by the Circadian Timing System, that synchronize them with the environment from external stimuli such as light. One of them is the secretion profile of most circulating hormones regulated by the hypothalamuspirtuitary axis, which controls functions essential for the survival and reproduction of organisms. The sagüi, Callithrix jacchus, one of the most studied species about their endocrine physiology, is an appropriate subject for evaluating the profile of plasma prolactin and cortisol of adult males and females born in captivity throughout the year. Three male and two adult femelas were housed individually and subjected to natural environmental conditions over two years. Blood samples were used to measure the circulating levels of both hormones by methods radioimmunoassay (RIA) and immunoassay (ELISA), respectively. The analysis during the year of the plasmatic values of both hormones test was performed by ANOVA for repeated measures, the correlation of Spearman, and the test of Friedman and Student's t-test. The levels of prolactin in plasma were higher during the months in which there is a greater incidence of births of baby in the colony, possibly serving for modulating the expression of the behavior of parental care in both sexes. The plasma cortisol showed a lift in anticipation of the station with the highest birth rate and may be associated with the preparation of individual participation in caring for the baby, and also with the establishment of emotional bond between reproductive partners. Thus, this study shows that, despite the variations observed in the environment in which the animals live, plasma levels of prolactin and cortisol vary little throughout the year.